Stem Cell Therapy for Organ Failure - Somasundaram, Indumathi (Springer India : Imprint: Springer, 2014)
The book Stem Cell Therapy for Organ Failures edited by Dr. S. Indumathi demonstrates the in vitro and in vivo therapeutic strategies and applications of pre- and post-natal stem cells for treating the failures of various organ systems of our body in a wide perspective. It explores the past, present and the futuristic approach of the exciting field of stem cells and its intriguing properties involved in tissue repair and regeneration. The prime focus of this volume is to unravel the basic, advanced, therapeutic and translational approaches put-forth so far in the field of stem cells and regenerative medicine at research, pre-clinical and clinical levels. Stem cells have ushered in widespread interest and exciting possibilities for cell based therapies, albeit failures do prevail and small uncontrolled phase I/II studies are only signals generating, rather than definite proof of concept thereby limiting its applicability in curative therapeutics. Despite certain initiatives and meticulous untiring efforts, bringing this basic bench side research into advanced transitional bedside remains a challenge. Thus, this book embarked upon the expanding researches in these areas that seem decisive in improvising regenerative medical therapeutics, thereby leading to further path-breaking studies that cure all health challenges facing mankind. Overall, this book reveals the imperativeness of various stem cell sources and its utility in curative therapeutics.